Corrigendum to “Functional testing in a mouse stroke model induced by occlusion of the distal middle cerebral artery” [J. Neurosci. Methods 184 (2009) 95-103] - Lubjuhn, Judith; Gastens, Alexandra; von Wilpert, Gertrud; Bargiotas, Panagiotis; Herrmann, Oliver; Murikinati, Sasidhar; Rabie, Tamer; Marti, Hugo; Amende, Ivo; Hampton, Tom G.; Schwaninger, Markus (Journal of neuroscience methods, 2010)
The authors regret that in the above mentioned paper, the middle initial of the author Hugo Marti was omitted. Dr. Marti’s full name is printed above.
Online veröffentlicht am 18. November 2009
Gesehen am 19.04.2023